Acoustic Correlates of Focus Marking in Czech and Polish. (June 2019) - Hamlaoui, Fatima; Żygis, Marzena; Engelmann, Jonas; Wagner, Michael
Languages vary in the type of contexts that affect prosodic prominence. This paper reports on a production study investigating how different types of foci influence prosody in Polish and Czech noun phrases. The results show that in both languages, focus and givenness are marked prosodically, with pitch and intensity as the main acoustic correlates. Like Germanic languages, Polish and Czech patterns show prosodic focus marking in a broad range of contexts and differ in this regard from other fixed-word-stress languages such as French. This suggests that (a) Polish and Czech are similar to Germanic languages and are unlike Romance languages in marking a variety of types of focus prosodically; (b) there is no close correlation between fixed word stress and lack of prosodic focus marking because Polish, which has fixed stress on the penult, shows prosodic focus marking for all types of focus; and (c) there is no straightforward relationship between flexible word order and whether focus and givenness are prosodically marked, contrary to earlier claims, because both Czech and Polish, with their relatively flexible word order, are more similar to English than Romance languages.